Chapter Il sistema degli scambi nel Mediterraneo occidentale tra XIV e XV secolo e il porto di Roma - PALERMO, Luciano (Atti delle «Settimane di Studi» e altri Convegni, 2019)
Between the 14th and 15th centuries, a dense network of trade relations was active in the maritime basin of the western Mediterranean. The three regional areas that overlooked this sea, the Iberian and Provencal, the Italian and the African, and all the islands that were present in it, were equipped with numerous and important landing points and were connected by a dense network of exchanges. The essay takes into consideration the characteristics of this network of economic and cultural connections, and analyzes, particularly through the use of the Datini Archive, the role of the port of Rome in this system of exchanges and the links that merchants and bankers who acted in this city entertained with the Iberian mercantile centers.